Web Based Marketing: Islamic Versus Conventional Banks of Pakistan - Ahmed, Khaliq; Kha, Muhammad Imran; Jan, Muhammad Tahir (Indian Journal of Marketing, 2010)
(Dave Chaffey, 2005) defined e-marketing as: "Applying Digital technologies which form online channels (Web, e-mail, databases, plus mobile/wireless & digital TV) to contribute to marketing activities aimed at achieving profitable acquisition and retention of customers (within a multi-channel buying process and customer lifecycle) through improving our customer knowledge (of their profiles, behavior, value and loyalty drivers), then delivering integrated targeted communications and online services that match their individual needs". Online marketing is marketing on the Internet. It is a type of e-marketing, which in turn is a type of e-commerce. Electronic commerce (E-commerce) is simply referred to buying and selling using the Internet; and people immediately think of consumer retail purchases from companies such as Amazon. However, e-commerce involves much more than electronically mediated financial transactions between organizations and customers. E-Banking may include ATMs, wire transfers, telephone banking, electronic funds transfers and debit cards. The Internet offers the potential for safe, convenient new ways to shop for financial services and conduct banking business, any day, any time. However, safe banking online involves making good choices/decisions that will help you avoid costly surprises or even scams. In Pakistan, e-Banking has started taking off in recent years. E-commerce task force has been formulated and the Banks have expanded their online branch networks. In the past 2-3 years, banks have also launched Internet Banking and the internet banking is now improving with more sophistication and services for corporate banking customers. In Pakistan initially, internet banking was launched to provide a limited number of services. But in recent years, there has been greater understanding and development towards various services being offered by banks through internet banking. Generous funds were allocated to improve e-Banking infrastructure, HR, security and applications for various components of e-Payments. Financial sector has increased the budget over 200% during the last 5 years, with total spending over US 300/million/year. With the satisfaction of legal issues of security assurance and easy access, there is an increase in usage of internet banking. More than 50% of the total bank branches are now also available online. E-banking infrastructure in Pakistan is growing at a considerable pace and the total of online network branches are more than 2500. A recent addition in electronic transactions has been allowing clients to access their accounts to do fund transfers and remittances from any ATM (Waqas Danish, 2007). As far as Islamic banking is concerned, Islam was the basis of creation of an independent state within the undivided Indo-Pak Sub-Continent. All Constitutions of Pakistan have incorporated, within the principles of policy, the elimination of Riba as an important objective of the State policy.